Egg parasitoid attraction toward induced plant volatiles is disrupted by a non-host herbivore attacking above or belowground plant organs - Moujahed, Rihem; Frati, Francesca; Cusumano, Antonino; Salerno, Gianandrea; Conti, Eric; Peri, Ezio; Colazza, Stefano (Frontiers in Plant Science, 2014)
Plants respond to insect oviposition by emission of oviposition-induced plant volatiles (OIPVs) which can recruit egg parasitoids of the attacking herbivore. To date, studies demonstrating egg parasitoid attraction to OIPVs have been carried out in tritrophic systems consisting of one species each of plant, herbivore host, and the associated egg parasitoid. Less attention has been given to plants experiencing multiple attacks by host and non-host herbivores that potentially could interfere with the recruitment of egg parasitoids as a result of modifications to the OIPV blend. Egg parasitoid attraction could also be influenced by the temporal dynamics of multiple infestations, when the same non-host herbivore damages different organs of the same plant species. In this scenario we investigated the responses of egg parasitoids to feeding and oviposition damage using a model system consisting of Vicia faba, the above-ground insect herbivore Nezara viridula, the above- and below-ground insect herbivore Sitona lineatus, and Trissolcus basalis, a natural enemy of N. viridula. We demonstrated that the non-host S. lineatus disrupts wasp attraction toward plant volatiles induced by the host N. viridula. Interestingly, V. faba damage inflicted by either adults (i.e. leaf-feeding) or larvae (i.e. root-feeding) of S. lineatus, had a similar disruptive effect on T. basalis host location, suggesting that a common interference mechanism might be involved. Neither naïve wasps or wasps with previous oviposition experience were attracted to plant volatiles induced by N. viridula when V. faba plants were concurrently infested with S. lineatus adults or larvae. Analysis of the volatile blends among healthy plants and above-ground treatments show significant differences in terms of whole volatile emissions. Our results demonstrate that induced plant responses caused by a non-host herbivore can disrupt the attraction of an egg parasitoid to a plant that is also infested with its host.